No evidence for altered up- and downregulation of brain activity in visual cortex during illusory shape perception in autism. (August 2019) - Utzerath, Christian; Schmits, Iris C.; Kok, Peter; Buitelaar, Jan; de Lange, Floris P.
Abstract: Autism spectrum disorder (ASD) may be marked by an altered balance between sensory input and prior expectations. Because many illusions rely on integrating sensory input with prior information such as spatial context, individuals with ASD may therefore be less susceptible to visual illusions than typically developing (TD) individuals. Yet empirical evidence on the matter is rather divergent, varying depending on the type of illusion, study procedure, and population. Visual illusions lead to neural activity alterations in the visual system. In the so-called Kanizsa illusion, these are likely caused by top-down feedback to V1. Here we tested the hypothesis that a reduced susceptibility to illusions in ASD would manifest as diminished modulation of V1 activity by illusions, using functional magnetic resonance imaging (fMRI). We presented 22 adolescents with ASD and 22 age-, gender-, and intelligence-matched TD controls with displays that consisted of three circular inducers. These either formed an illusory triangle (Kanizsa illusion) or not. We identified regions in primary visual cortex (V1) that corresponded to (the visual field locations of) the illusory triangle and its inducers, and recorded their visual response. Previous research in healthy volunteers has shown a specific pattern of up- and down-regulation in regions of V1 that process the shape and inducers, respectively. Here, we replicated this pattern of up- and downregulation in V1, in both the TD and ASD groups, with no differences between groups. This suggests that illusory shape processing in primary visual cortex is equally present in ASD, suggesting unimpaired processing of spatial context.